2001
DOI: 10.1148/radiology.218.1.r01ja23157
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning Accuracy with the Laitinen Frame for Fractionated Stereotactic Radiation Therapy in Adult and Pediatric Brain Tumors: Preliminary Report

Abstract: The Laitinen stereotactic localizer is well tolerated with accurate reproducibility during stereotactic radiation therapy. Preliminary local control rates are consistent with those in other reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In particular, the accuracy of the Laitinen frame, 22 used for stereotactic radiotherapy treatment, was tested by several authors using CT or portal images of phantom and/or patients. Ashamalla et al 25 showed a three-dimensional relocation accuracy ͑mean distance variation͒ of 1,5 mm±0,8 mm on a phantom while Kalapurakal et al 26 reported variations of 1,0 mm±0,7 mm; 0,8 mm±0,8 mm; 1,7 mm±1 mm, respectively, along x, y and z directions when testing the system on patients. Finally, Miranpuri et al, 27 using repeated CT images of a phantom, reported a mean error of about 2 mm along the z direction.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the accuracy of the Laitinen frame, 22 used for stereotactic radiotherapy treatment, was tested by several authors using CT or portal images of phantom and/or patients. Ashamalla et al 25 showed a three-dimensional relocation accuracy ͑mean distance variation͒ of 1,5 mm±0,8 mm on a phantom while Kalapurakal et al 26 reported variations of 1,0 mm±0,7 mm; 0,8 mm±0,8 mm; 1,7 mm±1 mm, respectively, along x, y and z directions when testing the system on patients. Finally, Miranpuri et al, 27 using repeated CT images of a phantom, reported a mean error of about 2 mm along the z direction.…”
Section: Discussionmentioning
confidence: 99%
“…Various noninvasive frameless SRS systems have been evaluated. For example, a noninvasive frame (Laitinen frame) made of reinforced plastic and aluminum that is mounted into the patient's head by means of two earplugs and a nasal support has been used and its accuracy has been evaluated (3) . While this system was used for both children and adults, it still produced some discomfort, or pain in the ear and nose during treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this work is, differently from more common in vivo CT, 1-6 cone beam CT, 7,8 portal, [9][10][11] and kV ͑Refs. 12 and 13͒ imaging studies, the evaluation with anthropomorphic phantom of the isocenter repositioning error during the several treatment sessions in stereotactic radiotherapy ͑SRT͒, measuring this quantity through comparisons between calculated dose distributions and corresponding film blackening maps.…”
Section: Introductionmentioning
confidence: 99%